A novel fluorescent self-assembling material with gel properties: ion recognition and energy transfer. Issue 22 (25th May 2022) - Ma, Xinxian; Yue, Jinlong; Qiao, Bo; Wang, Yipei; Gao, Yang; Ren, Tianqi; Tang, Jiahong; Feng, Enke; Li, Zhenliang; Han, Xinning
Abstract : A novel fabrication strategy for preparing fluorescent materials has been proposed based on energy transfer system, which is composed of a supramolecular self-assembly complexes (DAF–Al 3+, Donor) and a dye (Acridine yellow, Acceptor). Abstract : A novel fabrication strategy for preparing fluorescent nanomaterials has been proposed based on supramolecular self-assembly complexes and energy transfer. Here a dual acylhydrazone-functionalized molecule (DAF) was designed and synthesized by a Schiff base reaction. In DMSO–H2 O binary solutions, the DAF could selectively identify Al 3+ and form supramolecular self-assembly complexes DAF–Al 3+ . Interestingly, by loading the dye acridine yellow G (AYG) as an energy acceptor, an efficient light-harvesting system was successfully fabricated based on the supramolecular self-assembly complexes DAF–Al 3+ (donors).